Diagnosing Magnetic Field Geometry in Blazar Jets Using Multi-Frequency, Centimeter-Band Polarimetry and Radiative Transfer Modeling - Margo Aller; Philip Hughes; Hugh Aller; Talvikki Hovatta (MDPI, 2022)
We use multi-frequency linear polarization observations from the University of Michigan blazar program (UMRAO), in combination with radiative transfer simulations of emission from a relativistic jet, to investigate the time-dependent flow conditions, including magnetic field geometry, in an example blazar OT 081. We adopt a scenario incorporating relativistic shocks during flaring, and both ordered axial and helical magnetic field components and magnetic turbulence in the underlying flow; these constituents are consistent with the observed periods of ordered behavior in the polarization intermixed with stochastic variations. The simulations are able to reproduce the global features of the observed light curves, including amplitude and spectral evolution of the linear polarization, during four time periods spanning 25 years. From the simulations, we identify the signature of a weak-to-strong helical magnetic field on the polarization, but conclude that a dominant helical magnetic field is not consistent with the UMRAO polarization data. The modeling identifies time-dependent changes in the ratio of the ordered-to-turbulent magnetic field, and changes in the flow direction and Lorentz factor. These suggest the presence of jet-like structures within a broad envelope seen at different orientations.